The Influences of Problem-Based Learning Model with Fishbone Diagram to Students's Critical Thinking Ability - Istikomah, Istikomah; Basori, Basori; Budiyanto, Cucuk (IJIE (Indonesian Journal of Informatics Education), 2017)
Problem-based learning is characterized by the existence of a real problem as the context wherein students learn critical thinking skills, problem-solving, and knowledge acquisition. The concept of critical thinking gains popularity to help students obtain the ability to conduct fact analysis, support opinion with an argument, and problem-solving. The majority of Indonesian vocational school students, however, have difficulty in developing critical thinking skills and problem-solving. This research was purportedly designed to evaluate the differences of students' critical thinking ability in response to the application of various problem-based learning model namely Fishbone diagram, problem-based learning model, and expository learning model. A quasi-experimental design was applied to assess students' critical thinking. The findings indicate that there was a significant difference in students' critical thinking ability responding to the learning models. In summary, the research proposes the problem-based learning as an alternative learning model to improve student’s critical thinking ability.